Study of Humic Acid Adsorption Equilibrium on Dual Nanofiber PMMA/PVDF - Muhammad Ali Zulfikar; Afdal Bahri; Muhamad Nasir (Program Studi Pendidikan Kimia FKIP Universitas Sebelas Maret, 2018)
The main objective of this study is to investigate the isotherm sorption of humic acid (HA) from aqueous solution onto dual nanofiber PMMA/PVDF. Batch adsorption experiments were carried out using HA solution as an adsorbate under variety of concentration in the range of 50-200 mg/L. The experimental data were analyzed by the Langmuir, Freundlich and Sips models of adsorption. The experimental results indicate that, the adsorption capacity of HA adsorption increases with an increase in the HA concentrations. The adsorption of HA onto dual nanofiber PMMA/PVDF agrees well with the Langmuir isotherm models with the maximum adsorption capacity was found to be 137.40 mg g-1 at concentration of 100 mg L-1.